Radiographic variations of maxillary and mandibular premolars with type V canal configuration - A cone-beam computed tomographic study - Faisal Alnassar; Waleed Almutairi; Yousef Al-Dahman (Wolters Kluwer Medknow Publications, 2021)
Introduction: Cone-beam computed tomography (CBCT) image properly provides enhanced and accurate information of root morphology, canal configuration, and its possible variations. The aim of this study was to calculate the average distance from the cementoenamel junction (CEJ) up to the canal terminus and the width of the canal at the area of the division of type V configuration (Vertucci's classification) in premolar teeth using CBCT. Materials and Methods: Sevend hundered and seven CBCT images of the mandibular and maxillary premolars were screened for having type V configuration. The distance from CEJ to canal terminus and the width of the canal in the area of the division were measured. Age and gender were also recorded. Data were statistically analyzed. The statistical significance level was set at P < 0.05. Results: Maxillary second premolar teeth exhibited the shortest median distance from CEJ to the point of separation of the canal (3.86 mm) and the smallest width at the area of division (mean 1.86 ± 0.33 mm). No significant differences were observed in the distance nor width between genders in all teeth (P = 0.662 and 0.465, respectively). Moreover, no correlation was found between age and distance nor age and width of the canal (P = 0.89 and 0.95, respectively). Conclusion: The measurements give a general guideline for a more quantitative approach to endodontic access preparation for premolar teeth with type V configuration.